Optical ,electrical ,and structurl properties of Mn doped Cds thin flims prepared by CBD - Alwan, Sajid H.; Hmood, Attala B.; Jedran, K. Abd Alhadi (الجامعة المستنصرية - كلية التربية, 2010)
رسبت أغشية كبريتيد الكادميوم على شرائح زجاجية ضمن وسط قاعدي بواسطة عملية الترسيب بالحمام الكيميائي. وتم تشويب الأغشية بالمنغنيز حيث غيرت تراكيز الإشابة من 0.05 إلى 0.5%. أن نقصان المقاومية وفجوة الطاقة ضهر بوضوح نتيجة التطعيم. حددت الخصائص البصرية لأغشية كبريتيد الكادميوم المرسبة بالحمام الكيميائي لاستخدام هذه الأغشية كنافذة بصرية للمواد الهجينة المستخدمة في النبائط الالكترونية – البصرية Cadmium sulphide films have been deposited on non conducting glass slides in an alkaline medium by a chemical bath deposition process. The manganese doping concentration was varied from 0.05 to 0.5 wt %, it apparently decreases the band gap and lowers the resistivity. All beneficial optical properties of chemically deposited CdS thin films for application as a window material in hetrojunction optoelrctronic devices are retained.
ملخص لبحث منشور باللغة الإنجليزية
Keywords: كبريتات الكادميوم -- الحمام الكيميائي -- النبائط الإلكترونية